QUO VADIS’ OU TESTAMENT STUDIES? ’N RESPONS - O’Kennedy, Danie (Scriptura, 2009)
This article responds to that of Prof Douglas Lawrie "Old Testament: Quo Vadis?" The author agrees with Lawrie’s focus on the historical and literal dimension of the Old Testament text as well as the important contribution by feminist Old Testament scholars. However, there are a few challenges that Old Testament studies have to face in future: Do the students come to the university with a historical consciousness? Do the students have the language abilities to appreciate the literary features of the Old Testament? What is the role of the Old Testament in an African context? What is the relationship between Old Testament and church? There is a saying: "If the church has problems with her doctrine, she listens to the New Testament. If the church has problems with her life, she listens to the Old Testament." We in South Africa are in desperate need for people to live the biblical values of humanity and social justice. Old Testament studies can make an important contribution. Some people say "Knowledge is power." We can change this saying to emphasize another aspect: "Knowledge is service." Old Testament scholars must accept the challenge to serve the academic world, the church and society with their knowledge of the Old Testament, otherwise the Old Testament will be a forgotten book and no-one will live its important values.